2014
DOI: 10.1038/nature13950
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a mammalian ryanodine receptor

Abstract: Ryanodine receptors (RyRs) mediate rapid release of calcium (Ca2+) from intracellular stores into the cytosol, which is essential for numerous cellular functions including excitation-contraction coupling in muscle. Lack of sufficient structural detail has impeded understanding of RyR gating and regulation. Here, we report the closed-state structure of the 2.3 MDa complex of the rabbit skeletal muscle type 1 RyR (RyR1), solved by single-particle cryo-electron microscopy at an overall resolution of 4.8 Å. We fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
428
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(459 citation statements)
references
References 54 publications
(62 reference statements)
15
428
1
3
Order By: Relevance
“…Similarly, FDB fibers displayed decreased, but not absent, SR Ca 2+ release in response to tetanic stimulation at the time when RyR1 was severely fragmented. The channel pore region of RyR1 is located close to the C-terminal of the protein, and even the smallest major fragments (60 kDa) observed 24 h after the HIIT exercise would include the pore (47,48). Our immunostaining experiments on dissociated mouse FDB fibers showed a striated pattern of RyR1 staining at the time of fragmentation, hence indicating the continued presence of functional RyR1 Ca 2+ pores in the SR membrane.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, FDB fibers displayed decreased, but not absent, SR Ca 2+ release in response to tetanic stimulation at the time when RyR1 was severely fragmented. The channel pore region of RyR1 is located close to the C-terminal of the protein, and even the smallest major fragments (60 kDa) observed 24 h after the HIIT exercise would include the pore (47,48). Our immunostaining experiments on dissociated mouse FDB fibers showed a striated pattern of RyR1 staining at the time of fragmentation, hence indicating the continued presence of functional RyR1 Ca 2+ pores in the SR membrane.…”
Section: Discussionmentioning
confidence: 78%
“…On the basis of the near-atomic resolution three-dimensional structure of RyR1, it has been proposed recently that the EF-hand Ca 2ϩ binding domain (Fig. 9) encompasses a Ca 2ϩ sensor or conformational switch that is important for the activation of RyR1 by cytosolic Ca 2ϩ (13)(14)(15). However, the significance of the EF-hand domain in the cytosolic Ca 2ϩ activation of the RyR2 channel is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gomez and Yamaguchi (11) have also shown that the EF-hand Ca 2ϩ binding domain in RyR1 is involved in Ca 2ϩ -dependent inactivation. Furthermore, a peptide that encompasses the EF1 and EF2 motifs has been found to bind to the intact RyR1 channel and altered the Ca 2ϩ dependence of [ 3 H]ryanodine binding (12 Recently, the three-dimensional structure of RyR1 has been solved at near-atomic resolutions by using cryo-electron microscopy and single particle analysis (13)(14)(15). These highresolution structures have provided unprecedented insights into the structure-function relationship of Ca 2ϩ regulation of RyR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With continued improvements in technology, these have culminated in three reports on RyR1 in closed states between 6.1 and 3.8 Å, allowing up to 70% of the structure to be built [2][3][4]. RyRs are clear members of the superfamily of six-transmembrane (6-TM) ion channels, containing a transmembrane region with a pore-forming domain with inner (S5) and outer helices (S6), and a 4-helix bundle (S1-S4) that resembles voltage-sensing domains in voltagegated channels.…”
mentioning
confidence: 99%